A Comparison of Several CFD Codes with Experimental Data in a Diffusing S-Duct (AIAA 2013-3796) - Delot, Anne-Laure; Scharnhorst, Richard (AAIA Conference Papers American Institute of Aeronautics and Astronautics, 2013)
The AIAA/ASME/SAE/ASEE Joint Propulsion Conference identifies and highlights how innovative aerospace propulsion technologies powering both new and evolving systems are being designed, tested, and flown. Technical topics include Flight next generation commercial aircraft, regional, and business jets, military applications, supersonic/hypersonic high speed propulsion applications, commercial and government-sponsored launch systems, orbital insertion, satellite, and interstellar propulsion. A paper on A Comparison of Several CFD Codes with Experimental Data in a Diffusing S-Duct (AIAA 2013-3796) presented at the 2013 Joint Propulsion Conference.